Pengembangan UMKM Dalam Menghadapi Pandemi Covid 19 - Antony, Antony (PT. Alahyan Publisher Sukabumi, 2024)
Development training in dealing with the COVID-19 pandemic is a form of training provided to MSME actors. The role of MSMEs will play a very important role in supporting economic activities both regionally and nationally. This service activity aims to provide development for MSME actors in dealing with problems in using technology to market their business results and the packaging of a product (packaging) as a result of their business will greatly affect consumer interest in buying it. This service activity uses training and mentoring methods that are carried out directly. The expected result of this community service activity is an increase in the understanding of MSME actors to market their business products online. All participants of this activity have participated in all training activities that were carried out directly and have been applied in all their activities.